Mixed convection in an Horizontal Rectangular Duct Including interior Circular Core with Time periodic Boundary Condition - H. Al-Hafidh, Manal (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
Numerical Investigation was done for steady state laminar mixed convection and thermally and hydrodynamic fully developed flow through horizontal rectangular duct including circular core with two cases of time periodic boundary condition, first case on the rectangular wall while keeping core wall constant and other on both the rectangular duct and core walls. The used governing equations are continuity momentum and energy equations. These equations are normalized and solved using the Vorticity-Stream function and the Body Fitted Coordinates (B.F.C.) methods. The Finite Difference approach with the Line Successive Over Relaxation (LSOR) method is used to obtain all the computational results the (B.F.C.) method is used to generate the grid of the problem. A computer program (Fortan 90) is built to calculate Nusselt Number (Nu) in steady state. The fluid Prandtl number is 0.7 Rayleigh Number 1<Ra<106, Reynolds number 1<Re<2000. For the range of parameters considered, results show that the time periodic boundary condition enhance heat transfer. It is also indicated in the results that heat transfer from the surface of the circle exceeds that of the rectangle duct. Comparisons with other research show good agreement.